PENYUSUTAN BERAT TUBUH BROILER PADA KEPADATAN KERANJANG YANG BERBEDA SELAMA PENGANGKUTAN DARI KABUPATEN MESUJI KE KABUPATEN LAMPUNG SELATAN PROVINSI LAMPUNG - Mario Wisnu Wicaksono; Khaira Nova; Dian Septinova; RR Riyanti (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This research aimed to determine rectal temperature and heart rate changes, and the percentage of body weight shortening of broiler during the transportation process with different densities in the box and to determine the best density in the box during the transportation process. This research was conducted on 24--25 February 2021, on the way from Mr. Wahyu's broiler cage, Tanjung Raya District, Mesuji Regency to Mr. Tukimin's broker cage, Natar District, South Lampung Regency. This research was conducted using data collection methods with different densities in the boxes treatments with three treatments of density in the box with 18, 20, and 22 broilers/box, each treatment was repeated 6 times. The variables observed were rectal temperature and heart rate changes, and the percentage of body weight shortening. Based on the descriptive analysis that has been carried out, the treatment of differences in density in the box made rectal temperature and heart rate changes, and the percentage of body weight shortening of broiler. Box density of 18 broilers/box gave the best results on the decrease in rectal temperature of 1.48 ºC, an increase in heart rate of 31.00 beats/minute, and the percentage of body weight shortening of 3.03% compared to the treatment of box density of 20 and 22 broiler/box during the transportation process. Keywords: body temperature, body weight shortening, box density, broiler, heart rate, physiological response, transportation.